Kerjasama Laos-Jerman terkait Pengurangan Emisi Gas Rumah Kaca melalui Inisiatif CliPAD - Permana Manuaba, Ida Bagus Aditya; Fasisaka, Idin; Widya Nugraha, A.A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research aims to describe Lao’s effort on resolving deforestations that occurs. Lao government assumes that domestic resources that it has is not capable to solving the issue. By the incompetence, Lao government looks for other options for resolving deforestations aside of domestic options. Lao sees that there is a REDD+ scheme that has great potentials to attract financial aid and cooperation partner. By using REDD+ Lao then establishes bilateral cooperation with Germany and form an initiative that named CliPAD to be a facilitator on both nation’s activity. However, activity that done by them through CliPAD then facing barriers from the governance issue. By using concept International Climate Cooperation and Earth System Governance. This research concludes that cooperation that initiated by both nations through CliPAD could be going back when the strong system governance is already formed in supporting deforestation activities that will be done. Keywords: Lao, Deforestation, REDD+, CliPAD